2020
DOI: 10.1186/s13011-020-00286-2
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and predictors of direct-acting antiviral treatment for hepatitis C among people receiving opioid agonist therapy in Sweden and Norway: a drug utilization study from 2014 to 2017

Abstract: Background: Treatment with direct-acting antiviral agents (DAAs) offers an opportunity to eliminate hepatitis C virus (HCV) endemic among people who inject drugs (PWID) and people enrolled in opioid agonist therapy (OAT) programs. The objective of this study was to estimate and to compare HCV treatment uptake after the introduction of DAAs among patients receiving OAT in Sweden and Norway. We also aimed to evaluate predictors of DAAs treatment among OAT patients in both countries. Methods: This observational s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…This group of patients has a significant disease burden and limited ability to utilize standard healthcare. In the area surrounding the included clinics, around half of PWID had chronic HCV at the start of follow-up [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…This group of patients has a significant disease burden and limited ability to utilize standard healthcare. In the area surrounding the included clinics, around half of PWID had chronic HCV at the start of follow-up [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis suggests that people ≥41 years old with chronic HCV-both Known Ab+ and New Ab+-are significantly more likely to complete treatment (particularly New Ab+ who are males ≥41 years old) compared to their younger counterparts, similar to previous studies that hypothesize that older OAT patients' lives and drug use are more stable combined with the realization that the possibility of serious liver disease from HCV increases with age. 38,51 It also suggests that OAT clinics are suitable environments to reengage Known Ab+ into care, regardless of age, further suggesting the importance of providing onsite DAA at these clinics.…”
Section: (A) (B)mentioning
confidence: 99%
“…Previous data, before the DAA era, showed that the overall lifetime uptake of HCV treatment among PWID on OAT was between 1 and 6% [ 34 36 ]. However, an observational study with data from the Swedish Prescribed Drug Registers noted an estimated cumulative DAA treatment uptake of 28% among OAT participants between 2014 and 2017 [ 37 ].…”
Section: Introductionmentioning
confidence: 99%